1991
DOI: 10.1126/science.1649495
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor: Does It Have a Role in the Binding of Herpes Simplex Virus?

Abstract: We found that purified radiolabeled HSV could bind as well or better to the FGF receptor-deficient A-1 cells as they could to the FGF receptor-positive 4-1 cells (Fig. 1). At every concentration, about twice as much virus bound per cell to the A-1 cells as to the 4-1 cells, in the absence of heparin. The binding was inhibited by heparin, as has been shown previously for the binding of HSV to permissive HEp-2 cells (6). Because the adsorption of HSV to cells requires the presence of cell surface heparan sulfate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
0
16
2
Order By: Relevance
“…It should be noted that CHO cells are markedly deficient in high affinity receptors for FGF (38,68) and yet are susceptible to HSV infection . Enhancement of FGF receptor expression by transfection of the appropriate gene into CHO cells does not enhance susceptibility of the cells to infection by HSV1(F) or HSV1(KOS) (55) . Thus, deficiency of FGF receptors does not account for the partial restriction of HSV infection observed for these HSV strains in control CHO cells.…”
Section: Hsv-1 (F)mentioning
confidence: 99%
“…It should be noted that CHO cells are markedly deficient in high affinity receptors for FGF (38,68) and yet are susceptible to HSV infection . Enhancement of FGF receptor expression by transfection of the appropriate gene into CHO cells does not enhance susceptibility of the cells to infection by HSV1(F) or HSV1(KOS) (55) . Thus, deficiency of FGF receptors does not account for the partial restriction of HSV infection observed for these HSV strains in control CHO cells.…”
Section: Hsv-1 (F)mentioning
confidence: 99%
“…However, in view of the tissue tropism of these viruses, virus entry cannot be controlled by these ubiquitous receptor molecules alone. The role of the fibroblast growth factor receptor as a more specific receptor for herpes simplex virus type I is an example where heparan sulfate also serves as an accessory molecule [7].…”
Section: Introductionmentioning
confidence: 99%
“…inhibition of lymphocyte proliferative responses to IL-1 and IL-2, inhibition of cytokine production, decreasing the interferon-enhanced expression of class II histocompatibility antigens, inhibition of cytokine-induced expression of the alternative complement pathway activator B) [8] could be responsible for a decrease in the inflammatory response. Kaner et al [21] proposed a specific interaction of HSV with the FGF receptor and concluded that this receptor may serve as a "portal" of cellular entry for the virion, an observation which was not confirmed by Shieh and Spear [27] when repeating the experiments. However, because of the recent demonstration by Yayon et al [33] that binding of FGF to heparan sulfate is obligatory for its interaction with the high-affinity receptor, we asked whether complete inhibition of viral access to both heparan sulfate and and the FGF high-affinity receptor would exert additional beneficial effects during the course of the in vivo infection.…”
Section: Discussionmentioning
confidence: 73%
“…A model of FGF-2 action in this case would be direct competition of the growth factor with the virion for binding sites on heparan sulfate proteoglycans, a prerequisite for HSV-1 adsorption and infectivity as demonstrated byWuDunn and Spear [32]. This interpretation was recently proposed by Shieh and Spear [27] to explain the inhibition of viral adsorption by FGF-2 in some cell lines in vitro. To evaluate this hypothesis further, we applied high doses of heparin to HSV-1 infected corneas.…”
Section: Discussionmentioning
confidence: 85%